(NmUZYKAL_NYE WE^ERA(B.(NaRIETY I FORTEPIANO(B.s (NNOTYs - (NdV(B.(NrOSSINI(B.s ((NsANKT(B-(NpETERBURG(B.s (NlAN_s (NpLANETA mUZYKIs, 2024)
(NdVOAKKINO ROSSINI (B(1792-1868) - (NWYDA@]IJSQ ITALQNSKIJ KOMPOZITOR(B.s
Keywords: (NaRIETTIs